Sipakalebbi sebagai Model Komunikasi Antarbudaya Etnis Bugis dan Etnis Konjo di Sulawesi Selatan, Indonesia: Sipakalebbi as an Intercultural Communication Model between the Bugis and Konjo Ethnic Groups in South Sulawesi, Indonesia - Riswandi, Riswandi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
This study aims to describe how Sipakalebbi serves as an intercultural communication model in fostering cultural acculturation between the Bugis and Konjo ethnic communities. This research employs a qualitative approach, utilizing intercultural communication perspectives. Data collection methods include observation and in-depth interviews. The data processing and analysis techniques involve three stages: data reduction, data presentation, and conclusion drawing. The results reveal that the Bugis and Konjo ethnic communities build their relationships with a high level of Sipakalebbi attitude in fostering cultural acculturation. This intercultural communication model of Sipakalebbi is supported by a strong sense of kinship between the two ethnic groups. Driven by three local principles, namely sipakatau (mutual respect), siammasei (mutual love), and siasseajingeng (brotherhood), it can be ensured that the Bugis and Konjo ethnic communities will not encounter difficulties or obstacles in fostering cultural acculturation between them.